Biology, Taxonomy, and Management of the Root-Knot Nematode (Meloidogyne incognita) in Sweet Potato - Gebissa Yigezu Wendimu (Advances in Agriculture)
Sweet potato is the seventh-ranked food crop produced after wheat, rice, maize, potato, barley, and cassava in the world. It is the most important root tuber crop in temperate, subtropical, and tropical areas of the world. It is grown for food, income-generating, and jobs for farmers and retailers. The important nutritional substances of sweet potatoes are ß-carotene and anthocyanins. However, the production and its valuable products are limited due to root-knot nematode parasitism. One of the most important destructive species of root-knot nematode to this crop is Meloidogyne incognita. The most destructive stage to sweet potato is at its second juvenile stage (J2). At this stage, it invades the roots and tubers of sweet potato highly in warm sandy soil conditions. It is an obligate plant-parasitic nematode. M. incognita caused significant yield loss to sweet potato in terms of quality, quantity, disturbing the process of photosynthesis and nutrient uptake through the formation of galling, establishing of its feeding sites, or induced galls that contain giant-feeding cells, and cracking of tubers and roots directly. It also reduces the market values of the infected tuber of sweet potato by downgrading the production values. The problem of quality and quantity losses to sweet potato by this pest is one of the major problems nowadays. It caused this problem alone or interaction with other plant-parasitic pathogens or through synergistic of fungi, bacteria, viruses, and others. Therefore, this review paper is focused on the sweet potato M. incognita biology, taxonomy, geographical distribution, and management measures.